Perancangan Prototype Sistem Informasi Akuntansi (SIA) pada PT XYZ - Martono (Jurnal PROCESSOR, 2022)
PT XYZ is a company that has many business fields such as retail up to financing. PT XYZ at this time, running its business PT XYZ also utilizes information technology in the form of a general computer-based information system, the result of this current system having weaknesses in terms of data security to the high potential for human error. This happened because system users must reprocess all the data using a separate system and open other files before finally being able to process a financial report. Due to this problem, the author finally conducted a study entitled the design of a prototype accounting information system (AIS) at PT XYZ. The accounting information system (AIS) which is the final result of this research will be explained using use case diagrams and class diagrams modeling. The final result of this research will be in the form of prototypes of an accounting information system (AIS) which describes the user's flexibility in managing data categories, users, income transactions, expenditure transactions, debts, receivables, reports related to financial transactions at PT. XYZ and view of the transaction recaps.